Keunikan Reduplikasi Bahasa Madura dalam Dialek Probolinggo - Haryas Harja Susetya, Hemas; Mardiyah, Ifatul; Zahro, Halimatus (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2020)
ABSTRACT Research on morphological studies that is the duplication of Madura language needs to be several in it, especially in the language of Madura itself such as the word, meaning, and also its use. The purpose of this research is to review the existence of duplication in the regional language that is (Madura language), which is only times by residents of certain regions. In this research, the object of research is the word re-(duplicate) in Bahasa Indonesia and Madura language. This research is the source of the theory of duplication and types of duplication. this research was conducted by qualitative method. It can be concluded that madura language is only limited to its users if it is in Indonesian language which in general indonesians understand Bahasa Indonesia which is the national language. The results of the study are Indonesian and Madura language has a form of di duplication that inhibits the same. In addition, it was also found that the process of duplication changes the sound that sounds meaning, dimly partialed, healed, intact especially in casual speech. Keywords: Reduplication; differences in reduplication of Madurese and Indonesian languages.